DIS Union of the Core and the Periphery - Velickovski, Igor; Stojkov, Aleksandar; Rajkovic, Ivana (International journal of economics and financial issues, 2017)
This paper investigates the drivers of shock synchronization using quarterly data for 27 European countries over the period 1999–2013 and taking into account the difference between core and peripheral euro area and European transition countries. The results from panel error-correction models suggest that the euro area core has not been a strong magnetizer of the shock convergence of peripheral and transition countries since the euro’s inception as a result of the offsetting effects of the various factors that affected the shock convergence process. In particular, the demand shock convergence was supported by the intra-industry trade developments and, to some extent, by the trade intensity, at least for the peripheral countries, but their effects were offset by divergent fiscal policies, production structure changes and financial flows. On the other hand, supply shocks registered a divergent tendency that was mainly driven by trade intensity flows and uncoordinated fiscal policies. These findings challenge the endogeneity hypothesis and support the specialization paradigm, which is concerning evidence for the future stability of the euro area.